(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Students need excellent pronunciation skills to succeed in their studies. Pronunciation skills are required to students this will help them in the future. A common mistake made by the students who are studying English as their second language is they are not paying enough attention to English Pronunciation. This underestimation of the importance of pronunciation is because the student considers the other aspects of the English language such as grammar, lexicology and vocabulary are important but not pronunciation.